IMPLEMENTASI PROSES PENYEWAAN DAN PENGIRIMAN BARANG MELALUI WEBSITE KERENT - Elizabeth Fiona Agnesia; Lukman Abdul Azizul Hakim (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The rapid development of information technology has significantly transformed the rental industry, particularly in the electronics sector. One sector that has undergone a major transformation is the rental industry, particularly electronics. With higher demand for electronic devices and lower frequency of usage, the option to rent has become increasingly attractive. However, the manual process of renting electronic goods is often faced with various obstacles. Complex inventory management, manual transaction processes, and lack of information transparency are some of the common challenges. This can lead to customer dissatisfaction, low operational efficiency, and difficulty in finding accurate information. To overcome these challenges, a website-based “Kerent” was established that is expected to help solve problems related to the rental process. By utilizing technology, it is expected to improve operational efficiency, provide a better customer experience, and increase customer trust. The implementation of the "Kerent" platform is expected to improve the effectiveness of goods rental and delivery processes.